Apologia for a Lemma - Gorman, W. M. (Review of Economic Studies, 1971)
Journal Article Apologia for a Lemma Get access W. M. Gorman W. M. Gorman London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 38, Issue 1, January 1971, Page 114, https://doi.org/10.2307/2296627 Published: 01 January 1971